The localization of ERα and ERß in rat testis and epididymis - Mehmet Gur, Fatih; Aktas, Ibrahim (Annals of Medical Research, 2021)
Aim: It is an indisputable fact that estrogens are essential for the normal functioning of the male reproductive system. Although there are many studies investigating the localization of estrogen receptor α (ERα) and estrogen receptor ß (ERß) in the testis and epididymis, there is no consensus between the results of these studies. Therefore, in this study, it was aimed to investigate the ERα and ERß expression pattern in testis and epididymis using immunohistochemical methods. Material and Methods: The testis and epididymis tissues removed from 3 adult rats after anesthetized with ether. Then the tissues fixed in Bouin's fixative. The tissues embedded in paraffin were cut 5 µm thickness with microtome and stained with immunohistochemical methods. Results: In the testis, ERα-positive immunostaining was observed in the nuclei of peritubular myoid cells and in the cytoplasm of Leydig cells. The germ cells other than spermatogonium and spermatid were ERα-negative. ERβ-positive immunoreaction was detected in the nuclei of spermatogonia, peritubular myoid cells and Leydig cells. The cells in which ERα and ERβ positive immunostaining were seen most intensively were spermatogonia. ER (α and ß) positive immunostaining in the epididymis was observed in epithelial cells and interstitial stromal cells. Although most of the epithelial cells (principal, basal, apical) were ERα and ER β positive staining, others were negative.Conclusion: The results obtained in this study showed that ERα and ERß are localized in somatic and germ cells in the testis and epithelial and stromal cells in the epididymis. In this study, it was observed that ERα and ERß staining intensity in spermatogoniums was higher than other cells. This result can be interpreted that estrogens perform their effects on the testis mainly through spermatogonia. The presence of ER (α and ß) in testis and epididymis, support the view that estrogens play an important role in the development and maintenance of male reproductive functions and fertility.
Keywords: Epididymis; estrogen receptor alpha; estrogen receptor beta; rat; testis